MCKite: A Multi-Producer Multicast Scheme in Named Data Networking - Yu Zhang; Yanbin Sun; Hongli Zhang (Dianxin kexue)
Named data networking（NDN）-a future internet architecture replacing hosts with named data as the core objects in the network layer and natively supports single producer- multi consumer multicast application pattern. However, the support of multi-producer application in NDN is still an open problem. MCKite-a multi producer multicast scheme in NDN was proposed. MCKite utilized rendezvous mechanism and stated in pending interest table （PIT）to construct paths to producers. MCKite made topological positions of producers transparent to other producers and consumers, so that routing/forwarding information bases didn't need to be created beforehand or be updated which reduced the complexity of protocol. MCKite was applied to an improved multi-producer data synchronization protocol and had been implemented in ndnSIM. Experiments show that MCKite has shorter stretch and less traffic cost compared to previous work.